Meningkatkan Komitmen Organisasional Dosen: Analisis Pengaruh Kepemimpinan Perguruan Tinggi dan Kepuasan Intrinsik & Ekstrinsik Dosen - Yulis Nuryanti; Dewiana Novitasari; Yunianto Agung Nugroho; Ahmad Fauji; Gazali Gazali; Masduki Asbari (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This study aimed to measure the effect of transformational leadership on organizational commitment of the lecturers of a privat higher education institution in Tangerang which are mediated by intrinsic and extrinsic job satisfaction. Data collection was done by simple random sampling to 151 population of employees. The returned and valid questionnaire results were 102 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that transformational leadership have a positive and significant effect on intrinsic and extrinsic job satisfaction. Intrinsic and extrinsic job satisfaction have a positive and significant effect on organizational commitment. Intrinsic and extrinsic job satisfaction have a significant effect as mediator between transformational leadership and organizational commitment. This new research proposed a model for building the organizational commitment among the lecturers of a privat higher education institution in Tangerang through enhancing transformational leadership with intrinsic and extrinsic job satisfaction as a mediator. This research could pave the way to improve the lecturer readiness in facing the era of education 4.0.